Distinguishing Pure Honey from Honey Adulterated with Added Sugar Using the LC–MS/MS Method - La Ode Sumarlin; Etyn Yunita; Agustina Senjayani; Vetty Megantari (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2026)
Honey adulteration through the addition of sugar such as liquid sugar, cane sugar, fructose, and glucose remains a major concern affecting honey quality and authenticity. This study aimed to differentiate pure honey, sugar-adulterated honey, and synthetic honey using a liquid chromatography tandem mass spectrometry (LC-MS/MS) fingerprinting approach. Samples included pure acacia (A), longan (K), and kapok/randu (N) honeys, their corresponding sugar-adulterated variants, and synthetic honey (S) as a negative control. The results demonstrated that LC-MS/MS fingerprints effectively distinguished pure honey from adulterated and synthetic samples. Pure honeys exhibited more complex and specific metabolite profiles, whereas sugar addition led to simplified chromatographic patterns dominated by sugar-related compounds. Fructose- and glucose-adulteration produced metabolite profiles most similar to synthetic honey, with randu honey showing the highest sensitivity to fructose addition. Fructosylated compounds such as N-(1-deoxy-1-fructosyl)phenylalanine (Fru-Phe) and isomaltol were identified as indicators of sugar addition and thermal processing. In contrast, biologically and botanically derived metabolites, including umbelliferone, indoleacrylic acid, hypoxanthine, O-glutarylcarnitine, cyclic melatonin, phenethyl tiglate, and indole-3-carboxaldehyde, reflected nectar origin and natural biological processes. The detection of phenanthrene-3,4-diol further indicated environmental influences on honey composition. Overall, integrating processing indicators with biological and botanical markers provides a comprehensive and reliable framework for honey authentication via LC-MS/MS fingerprinting.